Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Handphone Merek Xiomi - Wuri Purnamasari (CV. Aksara Global Akademia, 2024)
This study aims to determine and analyze the influence of brand ambassadors and brand image on Xiaomi products simultaneously and partially on consumer purchasing decisions on Xiaomi cellphones. This study uses primary data as a source of data obtained by distributing questionnaires in the form of google forms and distributed to 100 respondents. The population that is the object of this study is all consumers of Xiaomi brand cellphones. Sampling was carried out using a purposive sampling technique. Respondents came from all groups ranging from 17 years of age and above who knew or had been consumers of Xiaomi brand cellphone products. The testing tools in this study consisted of validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination coefficient tests. The results of the study showed that partially the brand ambassador variable influenced Purchasing Decisions with a significance value of 0.000 <0.05 or a tcount value of 4.056> ttable 1.985. Brand Image partially influences Purchasing Decision with a significance value of 0.000 <0.05 or a tcount value of 5.208> ttable 1.985. Simultaneously, brand ambassador and brand image influence Purchasing Decision with a significance value of 0.000 <0.05.